Low Free Triiodothyronine as a Predictor of Poor Prognosis in Patients With Myocardial Infarction With Non-Obstructive Coronary Arteries - Abdu, Fuad A.; Mohammed, Abdul-Quddus; Liu, Lu; Zhang, Wen; Yin, Guoqing; Xu, Bin; Xu, Siling; Xu, Yawei; Che, Wenliang (Frontiers in Endocrinology, 2021)
Background Low free triiodothyronine (fT3) level is strongly associated with poor prognosis in various patient populations. However, the role of fT3 in the risk of clinical outcomes in myocardial infarction with non-obstructive coronary arteries (MINOCA) has not been studied. Our study aimed to evaluate the association between low fT3 levels and the clinical outcomes of MINOCA patients. Methods A total of 218 MINOCA patients without a history of thyroid disease were enrolled in the study. Demographic, baseline clinical data, thyroid hormones, and other biochemical parameters were assessed in all patients. According to the fT3 levels, the present study was classified into two groups: the low fT3 group (fT3<3.5 pmol/L) and the normal fT3 group (fT3 3.5-6.5 pmol/L). The endpoint of the study was major adverse cardiac events (MACE). Results Fifty-nine patients were in the low fT3 group and 159 patients were in the normal fT3 group. Over the two years of follow-up, 36 MACE have occurred. The occurrence of MACE was higher in the low fT3 group compared with normal fT3 group (25.4% vs 13.2%; P=0.031). Kaplan-Meier survival curves showed a significantly increased risk of MACE in patients with low fT3 (log-rank P=0.027). Multivariable logistic regression analysis stated that high fT3 was independently associated with lower risk of MACE after two years of follow up (OR, 0.623; 95% CI, 0.399- 0.972; P=0.037). Conclusion Low fT3 levels were significantly associated with increased risk of MACE in patients with MINOCA. This finding suggests that the fT3 levels may serve as a potential biomarker in risk stratification of MINOCA patients.